The RAS‐related GTPase RHOB confers resistance to EGFR‐tyrosine kinase inhibitors in non‐small‐cell lung cancer via an AKT‐dependent mechanism. Issue 2 (22nd December 2016) - Calvayrac, Olivier; Mazières, Julien; Figarol, Sarah; Marty‐Detraves, Claire; Raymond‐Letron, Isabelle; Bousquet, Emilie; Farella, Magali; Clermont‐Taranchon, Estelle; Milia, Julie; Rouquette, Isabelle; Guibert, Nicolas; Lusque, Amélie; et al.
Abstract: Although lung cancer patients harboring EGFR mutations benefit from treatment with EGFR‐tyrosine kinase inhibitors (EGFR‐TKI), most of them rapidly relapse. RHOB GTPase is a critical player in both lung carcinogenesis and the EGFR signaling pathway; therefore, we hypothesized that it could play a role in the response to EGFR‐TKI. In a series of samples from EGFR‐mutated patients, we found that low RHOB expression correlated with a good response to EGFR‐TKI treatment while a poor response correlated with high RHOB expression (15.3 versus 5.6 months of progression‐free survival). Moreover, a better response to EGFR‐TKI was associated with low RHOB levels in a panel of lung tumor cell lines and in a lung‐specific tetracycline‐inducible EGFR L 858R transgenic mouse model. High RHOB expression was also found to prevent erlotinib‐induced AKT inhibition in vitro and in vivo . Furthermore, a combination of the new‐generation AKT inhibitor G594 with erlotinib induced tumor cell death in vitro and tumor regression in vivo in RHOB‐positive cells. Our results support a role for RHOB/AKT signaling in the resistance to EGFR‐TKI and propose RHOB as a potential predictor of patient response to EGFR‐TKI treatment. Synopsis: High RHOB levels in EGFR‐mutated lung tumors predict resistance to EGFR‐tyrosine kinase inhibitor (TKI) therapy. Combination therapy with an AKT inhibitor might restore drug sensitivity in RHOB‐positive patients. High RHOB expression levels are associated with resistance to EGFR‐TKI in lung cancer cell lines and patients harboring EGFR‐activating mutations and in an EGFR L 858R ‐driven lung cancer mouse model. Median progression‐free survival after EGFR‐TKI treatment is 15.3 months for patients with low RHOB tumor levels and 5.6 months for patients with high RHOB levels. RHOB induces EGFR‐TKI resistance by preventing AKT inhibition. AKT inhibition with the new specific inhibitor ipatasertib (G594) reverses RHOB‐induced resistance to EGFR inhibitor erlotinib in vitro and in vivo . Abstract : High RHOB levels in EGFR‐mutated lung tumors predict resistance to EGFR‐tyrosine kinase inhibitor (TKI) therapy. Combination therapy with an AKT inhibitor might restore drug sensitivity in RHOB‐positive patients.